2020
DOI: 10.21203/rs.3.rs-24866/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Desquamation In Kawasaki Disease And Its Relationship With Coronary Artery Abnormalities

Abstract: Background Desquamation of hands and feet is a common characteristic of Kawasaki disease (KD), and occurs in 68-98% of patients diagnosed with KD. In this study, we analyzed patients’ varying desquamation levels in their hands or feet, in correlation with clinical presentation, to assess the relationship.Method We retrospectively reviewed children with KD who had follow-up visits in Kaohsiung Chang Gung Memorial Hospital’s pediatric outpatient department (OPD) during 2018 and 2019. We analyzed their age, labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These studies suggested that the observed incidence of desquamation may be higher because of the lack of established diagnostic and treatment guidelines and the inconsistent use of IVIG at that time. However, two studies published after 2020 reported an incidence rate of 82%, thus making it challenging to conclude a significant decrease in the incidence of desquamation compared to that previously reported ( 6 , 25 ). During our study, the carefully observed group (group I) had a desquamation rate of 85%, which was not markedly different from the rate of 87% reported in Korea in 1980 ( 26 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…These studies suggested that the observed incidence of desquamation may be higher because of the lack of established diagnostic and treatment guidelines and the inconsistent use of IVIG at that time. However, two studies published after 2020 reported an incidence rate of 82%, thus making it challenging to conclude a significant decrease in the incidence of desquamation compared to that previously reported ( 6 , 25 ). During our study, the carefully observed group (group I) had a desquamation rate of 85%, which was not markedly different from the rate of 87% reported in Korea in 1980 ( 26 ).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have not established a clear correlation between desquamation, coronary anomalies, and thrombocytosis with coronary anomalies. Some papers have reported no association, while others suggest that more severe desquamation may correlate with fewer coronary complications, and increased thrombocytosis may be associated with a higher incidence of coronary complications ( 6 , 10 , 24 , 25 , 34 ). Our study has limitations in discussing the correlation between desquamation, thrombocytosis and coronary artery complications, and the outcomes of early treatment.…”
Section: Discussionmentioning
confidence: 99%